Association of hemoglobin and vitamin D status with depression and cognitive function in Iranian older adults - Sara Hamdamian; Mozhgan Moshtagh; Mitra Moodi; Farshad Sharifi (Archives of Gerontology and Geriatrics Plus, 2024)
Introduction: Depression in old age can be associated with other symptoms, such as anemia, and hypovitaminosis D, which could affect cognitive function. This research investigates the associations between depression, anemia, and vitamin D status with cognitive function in older Iranian adults. Methods: The current study was part of the community-based prospective cohort study of the Birjand Longitudinal Aging Study (BLAS). Individuals over 60 and their families were assessed through structured interviews with questionnaires such as the Patient Health Questionnaire, Mini-Mental State Examination, and lab tests such as hemoglobin and vitamin D levels. Results: Of 1418 older adults, 21.9 % (311) had cognitive dysfunction, and 46.9 % (663) had moderate to severe depression. The most significant risk factors of cognitive decline included ischemic stroke (OR: 3.74), depression (OR: 2.37, 3.45), female gender (OR: 2.73), and age (OR: 1.10), Education (OR: 0.13), and Physically activity (OR: 0.37).The results identified associations between depression and cognitive dysfunction with hemoglobin mean. Despite finding relationships between vitamin D status and depression, it was not significant for cognitive dysfunction. Conclusions: Our results indicated that the duration of hypovitaminosis D might be more important in cognitive function. Future longitudinal research could investigate the effectiveness of clinical nutrition, dietary type, and intake in managing depression and cognitive decline by reducing the risk of vascular events in older people.